Collaboration Between Teachers and Parents for the Mental Health of High School Students and Adolescents - Nabila Zulfa Fauziyyah; Naura Raysa Azkia Ahmad; Suparmi (Konsultan Jurnal Ilmiah Indonesia, 2026)
The significant increase in cases of depression and burnout makes the mental health of high school students a critical issue, fundamentally hindering their academic success and psychosocial well-being. The purpose of this study was to analyze and formulate an ideal model of collaboration between teachers and parents as a basis for comprehensive support. Data from five different scientific articles quantitative, qualitative, and editorial were synthesized to form a workable theoretical framework. The results of this review developed the Support Alliance model, which emphasizes that effective collaboration must be based on trust, competence, and two-way communication. Key findings emphasize that emotional support from the home environment is the most important factor, and this collaboration should include training in resilience and self-management skills to strengthen students' internal well-being. While the Support Alliance model has a strong conceptual foundation, this study identified significant shortcomings in its implementation, primarily due to the high resource requirements, the urgency of developing measurable operational guidelines, and the integration of professional clinical expertise in handling high-risk cases.